Quality management of repair production for disassembly of pressure coupling - Павлова, Анна Алексеевна; Лагода, Анна Николаевна (Technology audit and production reserves, 2015)
The problems of quality management of disassembly of pressure coupling for effective functioning of repair production are considered because the effective use of machinery and equipment is the high level of maintenance and repair, which affects product quality and production costs. A condition for quality disassembly is to preserve parts of the repaired product. Particularly complex disassembly of pressure coupling is complex if they large or design does not allow using simple mechanical pullers as well as compounds which, as a result of heavy operation, is one-piece steel. Quality and productivity disassembly of such compounds occurs only using induction heating. However, normative-technical provision of such technologies is virtually absent, which makes their use is not effective in energy costs. Therefore, the aim of the work was to determine and justify the principle of laying the foundations of normative and technical provisions of quality, energy-efficient and productive technology of repair production for example, disassembling connections with interference when using induction heating. The structural-parametric principle for creating a normative-technical provision, system of construction classifications of disassembled pressure coupling with heating parts in their inbox, unified operations based on the account settings, limiting quality of products and a mathematical model of the process of repair of thermal technologies on the example of disassembling connections with interference which can be used for quality control in the production of repair schemes for any pressure coupling.